Hydrogen Production through Alkaline Electrolyzers: A Techno‐Economic and Enviro‐Economic Analysis - Naqvi, Syed Arslan Hassan; Taner, Tolga; Ozkaymak, Mehmet; Ali, Hafiz Muhammad (Chemical engineering & technology, 2023)
Hydrogen production through an alkaline electrolyzer as well as a techno‐economic and enviro‐economic analysis are presented. The proposal of this innovative study is to generate hydrogen gas energy from an alkaline electrolyzer energy system. The prototype of this alkaline electrolyzer was developed by application of hydrogen production through alkaline electrolyzer optimization. This novel chemical mixture is made up from the combination of ammonia, ethyl alcohol, urea, and deionized or distilled water. The result proved to be a model study by emphasizing the annual profit of the alkaline electrolyzer of a simple payback period of the prototype system. A prototype of alkaline electrolyzer is designed and developed to produce oxyhydrogen gas through water electrolysis. An environmentally friendly prototype of an alkaline electrolyzer with high energy efficiency is manufactured, accompanied by techno‐economic calculations. Oxyhydrogen gas is produced through water electrolysis by the alkaline reaction with direct current feeding, due to the base electrolyte KOH in the alkaline electrolyzer. Factors for the enhancement of the performance were also evaluated.